PENGEMBANGAN GAME EDUKASI PIXEL ADVENTURE “TANTANGAN MASTERMIND MATEMATIKA: THE QUEST FOR NUMERIA” SEBAGAI ALAT BANTU PEMBELAJARAN MATEMATIKA DI KELAS X - Farhan; Nurmayanti; Madaling (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Mathematics lessons often have difficulty in motivating students and making them understand the concepts taught. One creative way to use it is through the use of educational games. The focus of this research is to create an educational game in Unity3D to teach mathematics to class X students. The game "Mathematics Mastermind Challenge: The Quest for Numeria" was created to enhance students' understanding of Mathematics in an exciting way. This research uses research and development (R&D) techniques in the ADDIE format. (Analysis, Design, Development, Implementation, dan Evaluation). From the results of the study, the game was rated "very valid" with a score of 85% and "very practical" with the score of 83.35%. Therefore, it is considered suitable for use in the process of learning Mathematics.